Magmatic-petrogenetic & structural relationships of the peninsula granite of the Cape Granite Suite (CGS) with the Malmesbury group, sea point contact, Saldania belt, South Africa - Mhlanga, Musa (University of Western Cape, 2021)
>Magister Scientiae - MSc === The Sea Point contact, Cape Town, South Africa, exposes the contact between the Neoproterozoic Malmesbury Group metasedimentary rocks of the Pan-African Saldania belt and the intrusive S-type Peninsula Granite of the Neoproterozoic-Paleozoic Cape Granite Suite (CGS). The exposure outcrops over an area of approximately 170 m × 60 m with the northern end of the exposure being characterized by the country rock–microgranite intrusive contact. Heading further south, the outcrop transitions to the main contact zone, which is a predominantly gradational zone marked by sheets of compositionally variable granitic injections (collectively referred to as hybrid granite phases) concordant to the country rock structure, before reaching the main pluton area comprising the voluminous coarse-grained porphyritic granite. Using a combined study incorporating field, structural, geochemical, isotopic and U-Pb geochronological data, the intrusive contact is investigated to determine the construction history of the pluton and delineate possible emplacement mechanisms.